The relationship between trust propensity, cynicism, OCB, CWB, trust in team and perception of ingroup and outgroup - Ho, Yi Ming (2022)
With teamwork being emphasised in today’s work environment, this study examined the relationships between trust in team, organisational citizenship behaviour (OCB), counterproductive work behaviour (CWB), trust propensity, and cynicism. Specifically, trust in team was proposed as a mediator between trust propensity and cynicism (predictors) and OCB and CWB (outcomes), while perception of ingroups and outgroups was examined as a moderator between trust in team and the outcomes. This study was carried out using cross-sectional correlational design and utilized archival data of 350 working adults from various organisations in Malaysia. Likert scale questionnaires were used to collect data of this study. IBM SPSS Statistics v23 and SPSS PROCESS v3.5 software were used to analyse the data in this study. Regression analyses found that trust in team predicted both OCB and CWB, and trust propensity and cynicism predicted trust in team. As for the mediations, trust in team mediated the relationship between trust propensity and OCB, as well as cynicism and OCB but not with trust propensity nor cynicism with CWB. Finally, results showed that perception of ingroups and outgroups did not moderate the relationship between trust in team and the outcomes. This study showed the importance of trust propensity and cynicism in workplace in predicting work behaviours. The results from this study are useful for organisations looking to improve trust and work behaviour in their organisations. Further implications of the study are discussed.